2016
DOI: 10.15761/bem.1000105
|View full text |Cite
|
Sign up to set email alerts
|

The impact of different commercial yeasts on quality parameters of Montenegrin red wine – Vranac and Kratošija

Abstract: The influence of three different commercial yeasts (BDX, BM4X4 and ICV D21), on quality parameters of wines from varieties Vranac and Kratošija were studied during two consecutive vintage years. The basic quality parameters of grape must (sugar content, total acidity, pH, tartaric and malic acid) and the wine quality parameters (alcohol content, total dry extract, glycerol, pH, total polyphenols and total anthocyanins) were determined after each phase of vinifications: after alcoholic and malolactic fermentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…The results of the measured pH values in our research are generally comparable to the results of a number of authors [ 71 , 79 , 80 ].…”
Section: Discussionsupporting
confidence: 91%
“…The results of the measured pH values in our research are generally comparable to the results of a number of authors [ 71 , 79 , 80 ].…”
Section: Discussionsupporting
confidence: 91%
“…The content of cis-resveratrol in Vranac and Kratošija wines inoculated with commercial yeast (0.47±0.03 mg/L and 0.57±0.03 mg/L) was similar, but lower values were observed in Cabernet Sauvignon (0.25±0.01 mg/L), which is in accordance with the results reported for Australian red wines [39] and with recent results by Pajović et al [38]. In Kratošija and Vranac wines, cis-piceid with 43.2 and 50.0% was the predominant stilbene present, followed by trans-piceid with 35.3% in Kratošija, 32.5% in Vranac, while the main stilbene in Cabernet Sauvignon wine was trans-resveratrol (45.6%).…”
Section: Stilbenes In Winesupporting
confidence: 91%
“…The composition of phenolic compounds in wine depends on many factors which include: grape variety, winemaking technology, level of maturation, breeding system, UV radiation and sunlight exposure, as well as phenolic reactivity during winemaking and ageing [27][28][29][30]. Besides, attention was paid on oenological and overall evaluation of wines from Montenegrin indigenous cultivars [15,20,[31][32][33].…”
Section: Phenolics Content After Alcoholic and Malolactic Fermentationmentioning
confidence: 99%
“…In addition, anthocyanins are involved in important reactions, such are polymerization, oxidation, and formation of new pigments during the process of winemaking and wine maturation. The total content of anthocyanins in wine can widely range depending on grape variety, from 32.5 to 1011 mg/L [71,111,112,119].…”
Section: Anthocyaninsmentioning
confidence: 99%
“…Investigating singular yeast strains, confirmed that the used starters have the ability to influence polyphenolic composition of wine. The importance of inoculation with commercial yeast starters, in order to modulate the content of total polyphenols in wine, was also highlighted [111]. Recently, Grieco et al [27] investigated the influence of autochthonous yeasts isolated from the grapes of varieties Primitivo and Negroamaro grown in the Apulia region, and they determined significantly higher total concentrations of stilbenes in wines of both varieties fermented with autochthonous yeast (18.40-67.78 mg/L) than with commercial ones (3.70-18.83 mg/L).…”
Section: Changes During Alcoholic Fermentationmentioning
confidence: 99%